All Fall Down : a Novel - Weiner, Jennifer (New York : Atria Books, 2014)
"Allison Weiss has a great job...a handsome husband...an adorable daughter...and a secret. Allison Weiss is a typical working mother, trying to balance a business, aging parents, a demanding daughter, and a marriage. But when the website she develops takes off, she finds herself challenged to the point of being completely overwhelmed. Her husband's becoming distant, her daughter's acting spoiled, her father is dealing with early Alzheimer's, and her mother's barely dealing at all. As she struggles to hold her home and work life together, and meet all of the needs of the people around her, Allison finds that the painkillers she was prescribed for a back injury help her deal with more than just physical discomfort--they help her feel calm and get her through her increasingly hectic days. Sure, she worries a bit that the bottles seem to empty a bit faster each week, but it's not like she's some Hollywood starlet partying all night, or a homeless person who's lost everything. It's not as if she has an actual problem. However, when Allison's use gets to the point that she can no longer control--or hide--it, she ends up in a world she never thought she'd experience outside of a movie theater: rehab. Amid the teenage heroin addicts, the alcoholic grandmothers, the barely-trained "recovery coaches," and the counselors who seem to believe that one mode of recovery fits all, Allison struggles to get her life back on track, even as she's convincing herself that she's not as bad off as the women around her. With a sparkling comedic touch and tender, true-to-life characterizations, All Fall Down is a tale of empowerment and redemption and Jennifer Weiner's richest, most absorbing and timely story yet"--
Keywords: Women drug addicts -- Fiction -- Rehabilitation; Self-realization in women -- Fiction; FICTION / Contemporary Women; FICTION / Literary; FICTION / General; Domestic fiction